KONSEP KELUARGA MAṢLAḤAH PERSPEKTIF LEMBAGA KEMASLAHATAN KELUARGA NAHDLATUL ULAMA (LKK NU) - Salim, Mujibburrahman (Al-Mazaahib: Jurnal Perbandingan Hukum, 2017)
The family is the main foundation in building a strong and integrity Muslim society. In addition, the family is the smallest part of society that determines the progress or decline of a society, therefore it takes the concept of a strong family and in accordance with the circumstances of a plural society and a tolerant society. One of the family concepts that encompasses all these things is the concept of the maṣlaḥah family. The concept of the maṣlaḥah family according to the Nahdlatul Ulama Family Relief Society of Yogyakarta Special Region is a happy family whose basic needs are fulfilled and can also play an important role in society. Elements The formation of the maṣlaḥah family is maṣāliḥ usroh and maṣāliḥ 'āmmah. Utah usrah is achieved if it meets the elements of: the husband and wife are salih, good children, good association, and rizki enough. The mood of the Ammah in the family includes the fulfillment of all aspects of dharuriyat's maslahah, namely: the protection of religion, the protection of the soul, the protection of reason, the protection of the family, and the protection of property. If all these needs are fulfilled in the family, then create a family maslahah. Therefore, the fulfillment of all aspects above become the main priority in the formation of the maslahah family.